INTROVERSION IN ROWLING’S FANTASTIC BEASTS AND WHERE TO FIND THEM - Eka Selfany Gladys Hohary; Mister G. Maru; Imelda lolowang (Universitas Negeri Manado, 2020)
The aim of this research is to point out and explain about the introversion of Newt Scamander. This is a qualitative research, meaning that the data will not be presented through numbers but descriptions. In this research, the researcher uses J. K. Rowling’s screenplay Fantastic Beasts and Where to Find Them as the main source and other related sources such as books, online articles/journals, etc. while, in point out and explaining about the main character’s introversion, the researcher used psychoanalytic approach. After analysing the screenplay, the researcher finds that people should be allowed to be themselves and do what they are best at and not to be pressure to do something or being someone their not. Introversion is not a bad thing so instead of trying to change the introverts the society should try to embraces them. Understanding ones’ general attitude and function types is important to get a better understanding of ones-self.